A code of conduct to guide Indigenous-inspired spas. Issue 1 (2nd January 2020) - Ell, Laura D.; Pavelka, Joe P.
ABSTRACT: While best practices are provided for green spas, Indigenous tourism, and ecotourism, there has been an absence of a code of conduct for spas that aim to sustainably integrate culture. The need for guidelines unique to this niche spa sector is critical and timely given the post-COVID-19 demand by travellers seeking out more health-related benefits via wellness holidays. This paper reports on a study of international spa experts and Indigenous healers who incorporate ancient practices into spa experiences to provide benefits to clients through non-exploitative means. The result is a suggested code of conduct as well as a definition for spas offering services or rituals based on or inspired by Indigenous traditions. The code features several themes including risks; honouring culture; product development and training; client experience; as well as local empowerment. The benefits to Indigenous communities include meaningful employment and preserving ancient practices that are at risk of erosion. Benefits to clients include cross-cultural learning through oral history (storytelling) of traditions, and spa options that remedy stress or other health imbalances. The spa sector in turn benefits from guidance as to how to determine if and how cultural elements are suitable to incorporate into their spa menus of offerings.